The Church and the Use of Family Planning: A Case Study of the Presbyterian Church of Ghana, Ebenezer Congregation, Old Tafo - Samuel Adjei; Ebenezer Abrokwah; Isaac Boaheng (E-Journal of Humanities, Arts and Social Sciences)
The debate on whether the use of family planning methods within the Ghanaian Christian circle is a sin or not has been going on for quite some time now. The misunderstanding and misinterpretation of some Biblical texts like Genesis 1: 28 and Genesis 3 have led to this confusion in Ghanaian Christian circles. This paper used both empirical and non-empirical methodology and a qualitative research method with a case study approach to analyse some biblical texts; traditional concepts and contextualization of the use of family planning methods in the Presbyterian Church of Ghana, Ebenezer Congregation, Old Tafo. The findings of this paper are that: the Bible does not condone the use of family planning methods. Also, the Akan people of Ghana, do not frown on the use of family planning methods. The article concluded that family planning is not a sin from both biblical and Akan cultural perspectives. The authors recommended that: there should be extensive family planning education by the government; public education on the side effects of the use of some family planning methods; teaching family planning in the church will also be beneficial to members and there should be a critical reading of the Bible to guide the creation of church doctrines. The key findings from this paper contribute to Christian ethics by educating Ghanaian Christians on the concept of family planning.